Evaluasi Pelayanan Kesehatan Yang Diberikan Kepada Pasien Di Klinik Dokkes Polres Trenggalek Berdasarkan Aspek Service Quality - Lusyta Hermawan; Untung Slamet Suhariyono; Anis Ansyori (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2026)
Klinik Dokkes Polres Trenggalek is a primary healthcare facility serving police personnel, their families, and the general public under the National Health Insurance (JKN) scheme, which requires the clinic to maintain service quality amid a high volume of patient visits. Preliminary observations indicated that staff readiness in responding to patient needs and the perceived waiting time for services were not yet optimal. This study aims to evaluate the readiness of human resources, facilities and infrastructure, and service management, as well as to assess service quality based on the five dimensions of Service Quality (tangible, reliability, responsiveness, assurance, empathy). This research employed a descriptive qualitative approach involving six informants (the Clinic Head, a physician, a nurse, and three patients) through in-depth interviews, observation, and documentation, analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that HR readiness and SOP implementation at the clinic have run well, although limited parking space and stock shortages of certain medicines, particularly vitamins, were identified as recurring obstacles, consistently confirmed by all informants through source and method triangulation. Service quality across all five Service Quality dimensions was rated positively by patients. This study recommends improving parking facility management and medicine availability toenhance the overall service quality of Klinik Dokkes Polres Trenggalek.